(untitled) (Journal of Pharma Insights and Research, 2025)
Mucoadhesive drug delivery systems offer better therapeutic efficacy through prolonged contact with mucosal surfaces. The interaction between mucoadhesive polymers and the mucin layer enables improved drug bioavailability while overcoming limitations of conventional formulations such as rapid clearance and frequent dosing requirements. Recent developments in polymer science have introduced stimuli-responsive, biodegradable, and multifunctional polymers that enable precise control over drug release kinetics. Various mucosal routes including buccal, nasal, ocular, vaginal, and rectal have shown distinct advantages in bypassing hepatic first-pass metabolism. Novel techniques involving nanostructured carriers, polymer conjugates, and hybrid systems have further improved site-specific targeting capabilities. Smart polymers and bioinspired designs are enabling the development of personalized drug delivery platforms with improved patient compliance. The mechanisms of mucoadhesion, involving initial contact and consolidation phases, are governed by multiple physicochemical factors including polymer molecular weight, chain flexibility, and surface chemistry. Current research focuses on optimizing polymer properties and developing innovative formulation strategies to improve therapeutic outcomes across diverse clinical applications.